Development and Validation of RP-HPLC Method for the Simultaneous Estimation of Lansoprazole, Clarithromycin and Tinidazole in Combined Dosage Form - Dadhich, Bharat; Goyal, Rakesh; Agarwal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2021)
Analytical chemistry is one of the supreme branches of science which deals with the separation, identification and quantification of various natural and chemical compounds. It includes both qualitative and quantitative analysis. Quantitative analysis is having importance from the point of pharmaceutical chemistry. Quantification methods include chromatographic techniques, spectrophotometery, fluorimetery etc. One of the most popular method for quantitative analysis is High Performance Liquid Chromatography (HPLC). In this article, a reverse phase – HPLC method was developed for the simultaneous determination of Lansoprazole, Clarithromycin and Tinidazole in combined dosage form and validation of the developed method. The development of method includes selection of mobile phase, chromatographic method and wavelength whereas validation involves the parameters like linearity, accuracy, precision, Limit of detection (LOD), Limit of Quantification (LOQ), robustness, system suitability of the developed method. The result showed that the developed method is best fitted to the simultaneous determination of Lansoprazole, Clarithromycin and Tinidazole and validated as per standards.